Mapping of a non-spatial dimension by the hippocampal–entorhinal circuit - Aronov, Dmitriy; Nevers, Rhino; Tank, David W. (Nature (London), 2017)
Cells in the hippocampal–entorhinal circuit, which fire in response to navigational variables such as location or speed, are shown also to encode continuous, task-relevant but non-spatial variables such as sound frequency. Mapping sound in the brain (Tank 21692, Bio Letter) Map-like representations of physical space have been well-documented in the hippocampus by studies of spatial navigation, but it is unclear whether this spatial representation is part of a more general mechanism for encoding other continuous variables, such as sound. Here, David Tank and colleagues recorded from rat hippocampal neurons while they manipulated a joystick to control sound output along a continuous frequency scale. Neurons encoded for all aspects of this task and formed discrete firing fields in response to specific sound frequencies. The hippocampal cells representing this auditory axis overlapped with cells representing space during navigation. The authors suggest that representation mechanisms similar to those used during navigation may encode variables in a broader range of cognitive processes. During spatial navigation, neural activity in the hippocampus and the medial entorhinal cortex (MEC) is correlated to navigational variables such as location 1 , 2 , head direction 3 , speed 4 , and proximity to boundaries 5 . These activity patterns are thought to provide a map-like representation of physical space. However, the hippocampal–entorhinal circuit is involved not only in spatial navigation, but also in a variety of memory-guided behaviours 6 . The relationship between this general function and the specialized spatial activity patterns is unclear. A conceptual framework reconciling these views is that spatial representation is just one example of a more general mechanism for encoding continuous, task-relevant variables 7 , 8 , 9 , 10 . Here we tested this idea by recording from hippocampal and entorhinal neurons during a task that required rats to use a joystick to manipulate sound along a continuous frequency axis. We found neural representation of the entire behavioural task, including activity that formed discrete firing fields at particular sound frequencies. Neurons involved in this representation overlapped with the known spatial cell types in the circuit, such as place cells and grid cells. These results suggest that common circuit mechanisms in the hippocampal–entorhinal system are used to represent diverse behavioural tasks, possibly supporting cognitive processes beyond spatial navigation.